RESEARCH RESULTS OF FLOW HYDRAULIC AND SLUDGE SEDIMENT REGIME IN A RIVER WITHOUT A DAM - Norkulov Bekhzod Eshmirzaevich; Kalandarova Dilsuz Abdujamilevna (American Journals Publishing, 2022)
In this article, the analysis of the results of the field research conducted to assess the hydraulic and turbidity regime of the water flow in the area of the damless water intake project in the middle stream of the Amudarya, and the speed of the sedimentation processes of the turbidity in the river to the head of the water intake channel, based on the hydrodynamic parameters of the river in order to prevent deformation processes, was determined.
Keywords: stvor, uzan, water level, depth, hand lot, reka, discharge, downstream.